Intercollaboration Scouting Activities and Learning Outcomes of Sociology-Oriented for Civics Education - Ahmad Al Al Yakin; Heni Nopianti; Sumarto Sumarto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research discusses the inter collaboration between scouting activities and civic learning outcomes for students at SMP Negeri 2 Polewali Mandar, which is known based on the observations of students on the learning outcomes of Pancasila and civic education, which are classified as a low category. Therefore, through scouting activities to train talents, social interaction, build social communities in learning, self-confidence and independence in learning, and determine their destiny, Scout activities aim to help reduce learning difficulties, which, of course, affect the learning outcomes studied in this study. Talents honed through scouting activities can improve student learning outcomes in the Civics subjects contained in this study. This study aims to answer the question: what is the relationship between scout activities and civic learning outcomes for grade IX students? This research method uses quantitative methods. The population of this study was grade IX students of SMP Negeri 2 Polewali Mandar, totalling 201 students, consisting of 7 groups. The sampling technique used a random sampling system, with the research sample totalling 29 students. The research instruments were observation, civics learning outcomes, and the value of Scouting activities. Data collection is done by reducing information, displaying information, verifying, and concluding. Information collected through learning outcomes and scout activities was then analyzed using the SPSS 2.0 application. The results showed that there was a relationship between scout activities and learning outcomes. Data analysis was carried out using inferential statistical analysis techniques, namely correlation analysis. The results showed that there was a relationship between scout activities and learning outcomes as measured by r table 0.03 and r arithmetic 0.529. This proves significantly that Ha is accepted. So it can be said that the intercollaboration of scouting activities followed by students has a positive relationship with civic learning outcomes.